Optimization of Surface Roughness and MRR in Powder Mix EDM Die-Sink for Inconel 718 using RSM - M. Ahsan Ul Haq; Salman Hussain; Wasim Ahmad; Mirza Jahanzaib; Waseem Iqbal; Saira Shehzadi (Journal of Basic & Applied Sciences, 2018)
Product quality depends on the surface quality of the machined part and machining performance relay on the production rate of the process. Whereas surface quality of a part is based on surface roughness (SR) and production rate depend on the material removal rate (MRR). Minimum surface roughness and maximum MRR are of great value in the field of manufacturing. In powder mix Electrical Discharge Machined (EDM) selection of input parameters and their ranges are of great value because its helps to achieve the optimize values of the SR and MRR. This study contains the effect of four input variables; pulse on time (Pon), discharge current (DC), pulse off time (Poff) and powder concentration of EDM on SR and MRR of Inconel 718. Response Surface Methodology (RSM) center composite design (CCD) and Analysis of Variance (ANOVA) are used with 5% significant coefficient. It was observed that DC significantly affects the SR and MRR followed by the Pon.